Carbon nanomaterial loaded with magnesium oxide and elemental copper as well as preparation method and application of carbon nanomaterial
The preparation of carbon nanomaterials loaded with magnesium oxide and elemental copper through solvent thermal synthesis and high-temperature pyrolysis methods, solving the problems of tumor recurrence and slow wound healing in melanoma treatment, realizing the coordinated anti-tumor of photothermal and alkaline and promoting wound repair effect.
Patent Information
- Application Number
- CN202311030577.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-21
AI Technical Summary
The treatment of melanoma is facing the problems of tumor recurrence, wound infection and slow healing. The existing photothermal therapy has limited effect and requires combined with other therapies.
The copper-doped magnesium-based metal organic framework was synthesized by solvent heat, and carbon nanomaterials loaded with magnesium oxide and elemental copper were prepared by high-temperature pyrolysis to achieve the preparation of carbon nanomaterials.
Through the synergistic effect of photothermal and alkaline microenvironment, this material significantly enhances the anti-tumor effect, and has the versatility to promote wound repair and antibacterial, meeting the dual needs of melanoma treatment and repair.
Smart Images

Figure CN119488590A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a carbon nanomaterial loaded with magnesium oxide and elemental copper, and a preparation method and application thereof, and specifically to a carbon nanomaterial loaded with magnesium oxide and elemental copper, which is prepared by firstly synthesizing a copper-doped magnesium-based metal organic framework by solvent thermal synthesis and then further treating the nanomaterial by high-temperature pyrolysis to form a carbon nanomaterial loaded with magnesium oxide and elemental copper, and belongs to the field of nanomedical technology. Background Art
[0002] Melanoma is a common malignant tumor. The main treatment method at present is surgical resection. However, there are still clinical problems such as tumor recurrence, wound infection and difficulty in wound healing after surgery. Therefore, the development of multifunctional nanomaterials with anti-tumor, antibacterial and wound repair functions is expected to meet the dual clinical needs of melanoma treatment and repair. Photothermal therapy (PTT) is a new type of minimally invasive tumor phototherapy that has developed rapidly. It uses the strong absorbance and high photothermal conversion efficiency of photothermal agents (PTAs) in the near-infrared light band (wavelength range 700-1300nm) to convert light energy into heat energy, so that the temperature of local tumor tissue increases to 40-45℃ (thermal therapy) or above 45℃ (thermal ablation), eventually leading to tumor cell degeneration and necrosis. However, due to the complexity of the tumor environment, the therapeutic effect of PTT is limited, and other therapies need to be combined to achieve better anti-tumor effects.
[0003] The acidic microenvironment of tumors is the result of abnormal metabolism of tumor cells. Under aerobic conditions, most normal differentiated cells produce ATP by promoting oxidative phosphorylation through the mitochondrial tricarboxylic acid (TCA) cycle after glycolysis, and only produce lactic acid under anaerobic conditions. Tumor cells obtain abnormally much energy from aerobic glycolysis, converting most of the glucose directly into lactic acid, forming an acidic microenvironment of tumors. Antiacid therapy based on neutralizing acid or consuming lactic acid has been shown to have certain anti-tumor effects, and can further enhance the anti-tumor effect by reversing the tumor immunosuppressive microenvironment and tumor cell chemotherapy resistance. Therefore, the preparation of photothermal nanomaterials with anti-acid function is expected to achieve the synergy of photothermal therapy and anti-acid therapy and enhance the anti-tumor effect. Summary of the invention
[0004] In view of the problems of tumor recurrence and slow wound healing caused by bacterial infection faced in the clinical treatment of melanoma, the present invention provides a carbon nanomaterial loaded with magnesium oxide and elemental copper, which can achieve anti-cancer and antibacterial effects and promote skin repair, as well as a preparation method and application thereof.
[0005] In one aspect, the present invention provides a carbon nanomaterial loaded with magnesium oxide and elemental copper, wherein the carbon nanomaterial loaded with magnesium oxide and elemental copper comprises: carbon element, oxygen element, magnesium element and copper element; wherein the magnesium element exists in the form of oxide, and the copper element exists in the form of elemental copper; Preferably, the content of magnesium in the carbon nanomaterial loaded with magnesium oxide and elemental copper is 6.0 at% to 8.0 at%, and the content of copper is 0.1 at% to 0.5 at%.
[0006] In the present disclosure, magnesium in the carbon nanomaterial loaded with magnesium oxide and elemental copper is an essential nutrient element for the human body and has good biocompatibility. 2+ It can promote wound repair by affecting DNA replication, RNA transcription, ribosome assembly, and the opening and closing of ion channels. After magnesium oxide reacts with water, it can not only release a large amount of magnesium ions, but also create an alkaline microenvironment to achieve acid-resistant treatment of tumors. In addition, copper exhibits excellent surface plasmon resonance effect in the ultraviolet-visible-near infrared band, which can give carbon materials a higher photothermal conversion effect. On the other hand, copper itself also has excellent antibacterial effects and promotes tissue repair effects. Therefore, the construction of carbon nanomaterials loaded with magnesium oxide and copper can achieve alkalinity and photothermal synergistic anti-tumor effects, accelerate the tissue repair process, and prevent the occurrence of infection, which can better meet the dual clinical needs of melanoma treatment and repair.
[0007] Preferably, the content of magnesium in the carbon nanomaterial loaded with magnesium oxide and elemental copper is 6.5at% to 7.7at%; the content of copper in the carbon nanomaterial loaded with magnesium oxide and elemental copper is 0.2at% to 0.4at%. In this composite material, the introduction of elemental copper can improve the sample's ability to consume glutathione and its photothermal performance. It should be noted that further increasing the copper content does not improve the photothermal performance of the sample, because the surface plasmon resonance effect of elemental copper is not only related to the content of copper, but also closely related to its structure and composition. When the copper content is further increased, the particle size distribution of elemental copper and its distribution on the surface of magnesium oxide will change, which may lead to a weakening of the surface plasmon resonance effect. In addition, as the copper content increases, the pH value of the microenvironment produced by the hydrolysis of magnesium oxide decreases, which is not conducive to the anti-acid treatment of tumors.
[0008] Preferably, the carbon nanomaterial loaded with magnesium oxide and elemental copper has an amorphous structure and a particle size of 50 nm to 300 nm.
[0009] Preferably, under irradiation with a laser of wavelength of 700 nm to 1300 nm, the temperature of an aqueous solution of carbon nanomaterials loaded with magnesium oxide and elemental copper at a concentration of 200 μg / mL can rise from 25° C. to 60° C. within 1 min to 5 min.
[0010] On the other hand, the present invention provides a method for preparing a carbon nanomaterial loaded with magnesium oxide and elemental copper, wherein copper is doped into a magnesium-based metal organic framework material and pyrolyzed to obtain the carbon nanomaterial loaded with magnesium oxide and elemental copper.
[0011] Preferably, the preparation process of the copper-doped magnesium-based metal-organic framework material includes: mixing an organic ligand, a copper salt, a magnesium salt, a surfactant, a pH regulator and an organic solvent to obtain an organic precursor solution; reacting the obtained organic precursor solution at 80°C to 160°C for 12h to 36h to obtain a copper-doped magnesium-based metal-organic framework material.
[0012] Preferably, the organic ligand is selected from at least one of terephthalic acid, diaminoterephthalic acid, and 2,5-dihydroxyterephthalic acid; The surfactant is selected from at least one of sodium dodecylbenzene sulfonate, N-vinyl pyrrolidone and polyethylene glycol; The pH regulator is selected from at least one of ammonia water, sodium hydroxide and potassium hydroxide; The copper salt is selected from at least one of Cu(NO3)2·3H2O, CuCl2·2H2O, CuSO4·5H2O and Cu(CH3COO)2; The magnesium salt is selected from at least one of Mg(NO3)2·2H2O, MgCl2·6H2O, MgSO4·7H2O and Mg(CH3COO)2·4H2O; The molar ratio of the copper salt to the magnesium salt is 1:(1-50).
[0013] Preferably, the concentration of the organic ligand in the organic precursor solution is 0.1M to 0.5M.
[0014] Preferably, the concentration of the pH adjuster in the organic precursor solution is 0.01M to 0.1M.
[0015] Preferably, the concentration of the surfactant in the organic precursor solution is 0.1-1.0 mg / mL.
[0016] Preferably, the organic solvent is composed of a mixed solution of water and N,N-dimethylformamide (DMF); the volume ratio of water to N,N-dimethylformamide is 1:(10-20); The total volume of the organic solvent is 300-500 mL.
[0017] Preferably, the pyrolysis atmosphere is an inert atmosphere, and preferably the inert gas is argon; The pyrolysis temperature is 500°C to 1100°C, and the insulation time is 1h to 3h; Preferably, the heating rate of the pyrolysis is 5°C / min to 10°C / min.
[0018] On the other hand, the present invention provides an application of a magnesium oxide-loaded and copper-element carbon nanomaterial in the preparation of a material for treating melanoma and promoting skin wound repair. The introduction of elemental copper in the present invention can significantly enhance the photothermal performance of the magnesium oxide-loaded carbon nanomaterial and endow it with the ability to consume glutathione. The results of in vitro and in vivo experiments show that the composite material has a good multi-mode synergistic anti-melanoma effect of photothermal, alkalinity and glutathione consumption. In addition, the composite material can not only quickly kill bacteria through photothermal, but also release Cu 2+ The synergistic alkalinity achieves continuous antibacterial effect, thereby inhibiting bacterial infection and promoting the repair of infected wounds. The composite material can also promote cell migration and upregulate the expression of related genes to accelerate wound repair. In short, the material can meet the clinical needs of treating melanoma and promoting skin wound repair.
[0019] Beneficial effects: In the present invention, a copper-doped magnesium-based metal organic framework is first prepared by solvent thermal development, and then a carbon nanomaterial loaded with magnesium oxide and elemental copper is prepared by a high-temperature pyrolysis method. Due to the localized surface plasmon resonance effect of elemental copper nanocrystals, the photothermal performance of the material is significantly improved. Copper doping also gives the nanomaterial the ability to consume glutathione. Moreover, a small amount of copper doping does not affect the ability of magnesium oxide to hydrolyze and produce an alkaline microenvironment. The material can achieve synergistic treatment of melanoma through photothermal combined with anti-acid therapy. In addition, the nanomaterial can quickly kill Staphylococcus aureus and Escherichia coli through photothermal treatment, and can achieve long-term antibacterial effect by continuously releasing copper ions and synergizing alkalinity. More importantly, the nanomaterial can also promote cell migration and upregulate the expression of related genes to accelerate wound repair. The present invention prepares a multifunctional carbon nanomaterial with anti-cancer and antibacterial properties and promotes tissue repair, which can be widely used in the treatment of melanoma and the repair of skin wounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD patterns (a) and full XPS spectra (b) of a magnesium-based metal-organic framework (Mg-MOF), a magnesium-based metal-organic framework with different copper doping amounts (the first doping amount is marked as Mg / Cu-MOF-1, and the second doping amount is marked as Mg / Cu-MOF-2), and a copper-based metal-organic framework (Cu-MOF) are shown; Figure 2 XRD patterns of different metal organic frameworks after heat treatment are shown, wherein (a) shows the XRD pattern of Mg-MOF after heat treatment (labeled as MgO@C); (b) shows the XRD pattern of Mg / Cu-MOF-1 after heat treatment (labeled as MgO / Cu@C-1); (c) shows the XRD pattern of Mg / Cu-MOF-2 after heat treatment (labeled as MgO / Cu@C-2); (d) shows the XRD pattern of Cu-MOF after heat treatment (labeled as Cu@C); Figure 3 The Raman spectrum (a), TEM image (b), HAADF-STEM image and corresponding element distribution map (c) of MgO / Cu@C-1 are shown; Figure 4 (a) shows the pH values of MgO@C, MgO / Cu@C-1, MgO / Cu@C-2 and Cu@C solutions (200 μg / mL); (b) shows the pH values of MgO / Cu@C-1 solutions with different concentrations; Figure 5 The temperature rise curves (a) and the absorbance at 808 nm (b) of MgO@C, MgO / Cu@C-1, MgO / Cu@C-2, and Cu@C are shown; Figure 6 The cell activity (a) and intracellular GSH content (b) of B16F10 cultured under different conditions for 24 h are shown; Figure 7 The following are photos of Escherichia coli colonies cultured under different conditions for 20 minutes (a) and the corresponding antibacterial rates (b); photos of Staphylococcus aureus colonies cultured under different conditions for 20 minutes (c) and the corresponding antibacterial rates (d); Figure 8 The colony photos of the plates cultured with bacteria on MgO / C and MgO / Cu@C for 24 hours (a) and the corresponding antibacterial rates (b) are shown; Fig. 9 The effect of MgO / Cu@C on the migration of L929 is shown; Fig.10 The effect of MgO / Cu@C on gene expression is shown. DETAILED DESCRIPTION
[0021] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0022] In the present disclosure, the carbon nanomaterial loaded with magnesium oxide and elemental copper comprises carbon, oxygen, magnesium and copper, wherein the magnesium exists in the form of oxide and the copper exists in the form of elemental copper; preferably, the content of magnesium is 6.0 at% to 8.0 at%, and the content of copper is 0.1 at% to 0.5 at%. Due to the localized surface plasmon resonance effect of copper-based nanomaterials, the doping of elemental copper significantly improves the photothermal performance of the carbon nanomaterial loaded with magnesium oxide, and photothermal therapy of tumors can be achieved. In addition, the copper ions released by the copper element can effectively consume the glutathione overexpressed in the tumor microenvironment and reduce the resistance of tumor cells to oxidative stress. In addition, the alkaline microenvironment generated by the hydrolysis of magnesium oxide can consume lactic acid in the tumor microenvironment and achieve acid-resistant therapy.
[0023] The carbon nanomaterial loaded with magnesium oxide and elemental copper is an amorphous structure with a size of 50nm to 300nm.
[0024] Among them, under the irradiation of 700nm-1100nm wavelength laser, the temperature of the carbon nanomaterial aqueous solution loaded with magnesium oxide and elemental copper with a concentration of 200μg / mL can rise from 25℃ to 60℃ within 1min-5min.
[0025] The following is an exemplary description of a method for preparing a carbon nanomaterial loaded with magnesium oxide and elemental copper.
[0026] Terephthalic acid, diaminoterephthalic acid, at least one of 2,5-dihydroxyterephthalic acid, copper salt, magnesium salt, N-vinyl pyrrolidone, ammonia water and organic solvent are mixed to obtain an organic precursor solution. The copper salt is selected from at least one of Cu(NO3)2·3H2O, CuCl2·2H2O, CuSO4·5H2O and Cu(CH3COO)2; the magnesium salt is selected from at least one of Mg(NO3)2·2H2O, MgCl2·6H2O, MgSO4·7H2O and Mg(CH3COO)2·4H2O; the molar ratio of the copper salt to the magnesium salt is 1:(1-50). The concentration of 2,5-dihydroxyterephthalic acid in the organic precursor solution is 0.1M-0.5M. The volume of ammonia water in the organic precursor solution is 0.01-0.1M. The amount of N-vinyl pyrrolidone added to the organic precursor solution is 0.1 to 1.0 mg / mL. The organic solvent is composed of a mixed solution of water and N,N-dimethylformamide (DMF) in a volume ratio of 1:(10 to 20) with a total volume of 300 to 500 mL.
[0027] The organic precursor solution is reacted at 80° C. to 160° C. for 12 h to 36 h to obtain a copper-doped magnesium-based metal organic framework material.
[0028] The copper-doped magnesium-based metal organic framework is pyrolyzed to prepare a carbon nanomaterial loaded with magnesium oxide and elemental copper. The pyrolysis atmosphere is an inert atmosphere, and preferably the inert gas is argon; the pyrolysis temperature is 500°C to 1100°C, the heating rate is 5°C / min to 10°C / min, and the holding time is 1h to 3h.
[0029] In the present invention, the carbon nanomaterial loaded with magnesium oxide and elemental copper can be used in the fields of preparing melanoma therapeutic agents and later tissue repair materials.
[0030] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0031] Example 1 Weigh 0.2 g of Mg(NO3)2·6H2O, Cu(NO3)2·3H2O and PVP in different proportions (Table 1) and dissolve them in a mixed solvent (320 mL DMF and 25 mL H2O). Weigh 1.0 g of 2,5-dihydroxyterephthalic acid and add it to the above solution and stir for 10 min. Add 2.5 mL of NH3·H2O and continue stirring for 20 min. Transfer the solution to a reactor and place it in a 120°C thermostat for 8 h. After the reaction is completed, centrifuge the mixed solution at 6000 rpm for 5 min to obtain a precipitate. Wash the precipitate with ethanol 5 times to obtain the final product, and freeze-dry the product for use in the next step. According to the copper content from low to high, the products are labeled as Mg-MOF, Mg / Cu-MOF-1, Mg / Cu-MOF-2 and Cu-MOF.
[0032] Table 1 shows the metal raw material ratios and atomic percentages of metal elements of different samples: sample <![CDATA[Mg(NO3)2·6H2O(mg)]]> <![CDATA[Cu(NO3)2·3H2O(mg)]]> Mg(at%) Cu(at%) Mg-MOF 2560 0 13.02 0 Mg / Cu-MOF-1 2496 61 13.22 0.15 Mg / Cu-MOF-2 2430 122 12.09 1.26 Cu-MOF 0 2420 0 6.88
[0033] MgO / Cu@C was prepared by pyrolysis of Mg / Cu-MOF. The detailed synthesis steps are as follows: The porcelain boat loaded with Mg / Cu-MOF was placed in a tube furnace and heat treated in an Ar atmosphere (900°C). The heating rate was 5°C / min, the holding time was 120min, and the Ar flow rate was 3sccm (cm3 / min). The products obtained by pyrolysis of Mg-MOF, Mg / Cu-MOF-1, Mg / Cu-MOF-2 and Cu-MOF were named MgO@C, MgO / Cu@C-1, MgO / Cu@C-2 and Cu@C, respectively. The main components of the pyrolysis products are C, O, Mg and Cu. The element contents of different products are shown in Table 2.
[0034] Table 2 shows the atomic percentages of different elements in different samples: sample C (at%) O(at%) Mg(at%) Cu(at%) MgO@C 60.35 32.70 6.95 0.00 MgO / Cu@C-1 60.70 32.55 6.52 0.23 MgO / Cu@C-2 60.36 31.56 7.69 0.39 Cu@C 59.05 31.61 0.00 9.14
[0035] Figure 1(a) shows the XRD patterns of different samples. As the Cu content increases, the peak intensity of the characteristic peak of Mg-MOF gradually weakens, and the characteristic peak of Cu-MOF shifts, which may be due to the fact that the introduction of Cu affects the growth orientation of Mg-MOF. Figure 1 (b) shows the full XPS spectra of different samples. Mg-MOF is mainly composed of C, O, and Mg, Mg / Cu-MOF-1 and Mg / Cu-MOF-2 are mainly composed of C, O, Mg, and Cu, and Cu-MOF is mainly composed of C, O, and Cu. Due to the small amount of Cu, the XPS characteristic peaks of Cu in Mg / Cu-MOF-1 and Mg / Cu-MOF-2 are relatively weak.
[0036] Figure 2 The XRD patterns of different metal organic frameworks after heat treatment. The results show that after carbonization of Mg-MOF in Ar, a composite material composed of MgO and C (MgO@C) was obtained, after carbonization of Cu-MOF in Ar, a composite material composed of Cu and C (Cu@C) was obtained, and after carbonization of Mg / Cu-MOF-1 and Mg / Cu-MOF-2 in Ar, composite materials composed of MgO, Cu and C (MgO / Cu@C-1 and MgO / Cu@C-2) were obtained.
[0037] Figure 3 (a) The Raman spectrum of MgO / Cu@C-1 shows two main peaks of carbon, among which the D peak (1340 cm -1 ) corresponds to disordered carbon or defective graphite structure, and the G peak (1575 cm -1 ) is a typical feature of graphite, which once again confirms the existence of C structure in MgO / Cu@C. Figure 3 (b) and (c) show the TEM image and element distribution map of MgO / Cu@C-1. The results show that MgO / Cu@C-1 has an amorphous structure, and the C, O, Mg and Cu elements are evenly distributed. It is further determined that it is a composite material composed of MgO, Cu and C, and Cu and MgO are evenly loaded on the C skeleton.
[0038] Figure 4 is the pH value of the sample in PBS. Figure 4 As can be seen in (a), there is no significant difference in the pH values of MgO@C and MgO / Cu@C-1 solutions, both of which are about 9. The pH values of MgO / Cu@C-2 and Cu@C are significantly reduced, with the pH of Cu@C being only about 7.5. This shows that the introduction of a small amount of Cu will not affect the alkalinity of MgO@C, but the introduction of excessive Cu will reduce the pH value of the solution. This may be because the alkalinity of the solution is mainly formed by the hydrolysis of MgO, and the introduction of a small amount of Cu will not affect the content of MgO, while the introduction of excessive Cu will reduce the content of MgO. In addition, Figure 4As can be seen from (b), the alkalinity of MgO / Cu@C-1 solution is related to its concentration. The higher the concentration, the stronger the alkalinity.
[0039] Figure 5 (a) shows the heating curves of different samples under near-infrared light irradiation. MgO@C, MgO / Cu@C-1, MgO / Cu@C-2 and Cu@C all heated up significantly under 808nm NIR irradiation. The heating rates of MgO / Cu@C-1 and MgO / Cu@C-2 were significantly higher than those of MgO@C and Cu@C. Among them, the heating rate of MgO / Cu@C-1 was relatively faster, reaching about 55°C within 5 minutes. This may be related to the light absorption of MgO@C, MgO / Cu@C-1, MgO / Cu@C-2 and Cu@C at 808nm. Figure 5 As shown in (b), the absorbance values of different samples at 808 nm of MgO / Cu@C-1 have the following trend: MgO / Cu@C-1>MgO / Cu@C-2>MgO@C>Cu@C, which is consistent with the photothermal performance test results.
[0040] Embodiment 2: The in vitro antitumor properties of MgO@C and MgO / Cu@C with and without NIR irradiation were evaluated by detecting the activity of tumor cells (B16F10). The specific experimental methods are as follows: The cell activity was detected using an Alamar Blue (AbD serotec Ltd, UK) kit. First, cells were inoculated in a 96-well transparent plate and placed in an incubator for 24 h at a seeding density of 1×10 4 Then the original culture medium was replaced with fresh culture medium containing the material (200 μg / mL), and the material and cells were incubated for 2 h before near-infrared light irradiation with a power density of 0.4 W / cm 2 , the illumination time is 5min, and after the illumination ends, the cell culture plate is placed in a cell culture incubator for further incubation for 24h. Then, the cells are cultured with 10% AB dilution for 2h, and the fluorescence intensity value of each well is measured using an ELISA instrument, and the test wavelength is 560nm (Ex) / 590nm (Em). The corresponding cell inhibition rate is calculated according to the following formula: Wherein F represents the fluorescence intensity of the culture medium after the cells are co-cultured with the material; F0 represents the fluorescence intensity of the culture medium when the cells are not co-cultured with the material; and Fblank represents the fluorescence intensity of the culture medium containing only 10% Alamar blue.
[0041] Figure 6(a) shows the in vitro anti-melanoma effect of MgO@C and MgO / Cu@C. For the non-irradiated group (-NIR), both the MgO@C group and the MgO / Cu@C group have a certain killing effect on tumor cells, which is the alkaline anti-tumor effect. In addition, the anti-tumor effect of the MgO / Cu@C group is stronger than that of the MgO@C group. This is because MgO / Cu@C can consume GSH, while MgO@C cannot consume GSH, such as Figure 6 As shown in (b). After NIR application, the cell activity of the Control group and the MgO@C group did not change significantly, but the cell activity of the MgO / Cu@C group was close to 0. This is because MgO / Cu@C has a good photothermal effect, which once again confirms that Cu doping can enhance the photothermal effect of MgO@C. In addition, the photothermal effect of MgO / Cu@C can enhance its GSH consumption, thereby improving the anti-tumor effect.
[0042] Example 3 Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) were used to evaluate the antibacterial properties of MgO@C and MgO / Cu@C. The specific experimental methods are as follows: The sample and bacteria were diluted to a mixed bacterial solution (4 mL) of the corresponding concentration using PBS. The final concentration of the sample was 200 μg / mL and the inoculum density of the bacteria was 10 5 CFU / mL. 1 mL of the mixed bacterial solution was taken out and placed in a 24-well plate for photothermal and non-photothermal treatment. The light treatment group (+NIR) was to culture the mixed bacterial solution for 15 minutes and then irradiate it under 808nm NIR for 5 minutes (0.4W / cm 2 ). After the illumination is over, take out 100uL of the diluted bacteria for bacterial plating. Then, place the agar plate in a 37℃ incubator for about 18h, and finally take photos and record.
[0043] Figure 7 (a) and (b) are photos of Escherichia coli colonies cultured under different conditions for 20 minutes and the corresponding antibacterial rates. Figure 7 (c) and (d) are photos of the colonies of Staphylococcus aureus cultured under different conditions for 20 minutes and the corresponding antibacterial rates. The results show that there is no significant difference in the number of colonies between the Control group and the MgO@C group before and after NIR light irradiation, but the number of colonies of MgO / Cu@C is significantly reduced after NIR light irradiation, and the antibacterial rate is as high as 100%, which is due to the good photothermal properties of MgO / Cu@C.
[0044] The sample and bacteria were diluted to a mixed bacterial solution (4 mL) of the corresponding concentration using PBS. The final concentration of the sample was 200 μg / mL and the inoculum density of the bacteria was 10 5CFU / mL. Take out 1mL of mixed bacterial solution and place it in a 24-well plate. After 24 hours of co-culture, take out 100uL of diluted bacteria for bacterial plating. Then, place the agar plate in a 37℃ incubator for about 18 hours, and finally take pictures and record.
[0045] Figure 8 (a) and (b) are photos of the plate colonies of Escherichia coli and Staphylococcus aureus pre-cultured for 24 hours and the corresponding antibacterial rates. MgO@C has a significant inhibitory effect on bacteria, indicating that the alkalinity formed by MgO@C has a certain antibacterial effect. Compared with MgO@C, the antibacterial effect of MgO / Cu@C is further improved, and the antibacterial rate of MgO / Cu@C is as high as 100%, which is the result of the synergistic effect of alkalinity and Cu2+.
[0046] Embodiment 4: L929 cells were used to evaluate the effects of MgO / Cu@C on cell migration and gene expression. The specific experimental methods are as follows: The effect of MgO / Cu@C extract on L929 cell migration was evaluated by cell scratch test. L929 cells were seeded in 24-well plates (5×10 4 Cells / well) were cultured for 48 hours, and the cells formed a monolayer at the bottom of the well plate. A scratch was made on the cell monolayer with a 10μL pipette tip to simulate the incision wound, and then 1mL of culture medium (1% FBS) containing MgO / Cu@C (200μg / mL) was added to continue the culture. At the desired time point (6h), 500μL of 4% paraformaldehyde (PFA) solution (Sigma, USA) was added to each well to fix the cells. The cell nucleus was stained with 4',6-diamidino-2-phenylindole (DAPI), and observed and photographed under a fluorescence microscope.
[0047] RT-PCR experiments were used to evaluate the effects of MgO / Cu@C on the expression of genes related to angiogenesis and wound repair (VEGF, TGFβ, and COL1) in L929 cells. L929 cells were seeded in 6-well plates at a seeding density of 1×10 5cells / well; culture for 24 hours, replace the original culture medium with fresh culture medium containing MgO / Cu@C; co-culture the sample with cells for 24 hours, rinse twice with PBS, add Trizol to extract total RNA, and quantify the total RNA by UV-visible spectrophotometer (nanodrop 2000, Thermofisher, USA); reverse transcribe 1μg of total RNA into cDNA using st Strand cDNA synthesis supermix Kit (Yeasen, China); mix cDNA with SYBR Green Mastermix and primers to quantify the expression of target genes. Gene analysis uses GAPDH as the reference gene and is normalized, and the 2-ΔΔCT method is used for relative quantification.
[0048] Fig. 9 The results are for L929 cell migration. MgO / Cu@C significantly promoted L929 migration, which may be due to the fact that MgO / Cu@C can upregulate the expression of wound repair-related genes such as TGFβ, VEGF and COL1 in L929. Fig.10 shown.
[0049] Industrial applicability: The present invention prepares a carbon nanomaterial loaded with magnesium oxide and elemental copper with anti-cancer, antibacterial and repair-promoting effects, which can be widely used in treating melanoma and promoting skin wound repair.
Claims
1. A carbon nanomaterial loaded with magnesium oxide and elemental copper, characterized in that: The carbon nanomaterial loaded with magnesium oxide and single copper comprises: carbon, oxygen, magnesium and copper; wherein the magnesium exists in the form of oxide, and the copper exists in the form of single substance; Preferably, the content of magnesium in the carbon nanomaterial loaded with magnesium oxide and elemental copper is 6 at% to 8 at%, and the content of copper is 0.1 at% to 0.5 at%.
2. The carbon nanomaterial loaded with magnesium oxide and elemental copper according to claim 1, characterized in that: The content of magnesium in the carbon nanomaterial loaded with magnesium oxide and elemental copper is 6.5 at% to 7.7 at%; The content of copper element in the carbon nanomaterial loaded with magnesium oxide and elemental copper is 0.2at% to 0.4at%.
3. The carbon nanomaterial loaded with magnesium oxide and elemental copper according to claim 1 or 2, characterized in that: The carbon nanomaterial loaded with magnesium oxide and elemental copper has an amorphous structure and a particle size of 50nm to 300nm.
4. The carbon nanomaterial loaded with magnesium oxide and elemental copper according to any one of claims 1 to 3, characterized in that: Under irradiation of laser with a wavelength of 700nm to 1300nm, the temperature of an aqueous solution of carbon nanomaterials loaded with magnesium oxide and elemental copper with a concentration of 200μg / mL can rise from 25°C to 60°C within 1min to 5min.
5. A method for preparing a carbon nanomaterial loaded with magnesium oxide and elemental copper as claimed in any one of claims 1 to 4, characterized in that: The magnesium-based metal organic framework material is doped with copper and subjected to pyrolysis to obtain the carbon nanomaterial loaded with magnesium oxide and elemental copper.
6. The preparation method according to claim 5, characterized in that: The preparation process of the copper-doped magnesium-based metal organic framework material comprises: mixing an organic ligand, a copper salt, a magnesium salt, a surfactant, a pH regulator and an organic solvent to obtain an organic precursor solution; reacting the obtained organic precursor solution at 80° C. to 160° C. for 12 h to 36 h to obtain a copper-doped magnesium-based metal organic framework material.
7. The preparation method according to claim 6, characterized in that: The organic ligand is selected from at least one of terephthalic acid, diaminoterephthalic acid, and 2,5-dihydroxyterephthalic acid; The surfactant is selected from at least one of sodium dodecylbenzene sulfonate, N-vinyl pyrrolidone and polyethylene glycol; The pH regulator is selected from at least one of ammonia water, sodium hydroxide and potassium hydroxide; The copper salt is selected from at least one of Cu(NO3)2·3H2O, CuCl2·2H2O, CuSO4·5H2O and Cu(CH3COO)2; The magnesium salt is selected from at least one of Mg(NO3)2·2H2O, MgCl2·6H2O, MgSO4·7H2O and Mg(CH3COO)2·4H2O; The molar ratio of the copper salt to the magnesium salt is 1:(1-50).
8. The preparation method according to claim 6, characterized in that: The organic ligand concentration in the organic precursor solution is 0.1M to 0.5M; The pH adjusting agent concentration in the organic precursor solution is 0.01M to 0.1M; The surfactant concentration in the organic precursor solution is 0.1-1.0 mg / mL.
9. The preparation method according to claim 6, characterized in that: The organic solvent is composed of a mixed solution of water and N,N-dimethylformamide (DMF); the volume ratio of water to N,N-dimethylformamide is 1:(10-20); The total volume of the organic solvent is 300-500 mL.
10. The preparation method according to any one of claims 5 to 9, characterized in that: The pyrolysis atmosphere is an inert atmosphere, and preferably the inert gas is argon; The pyrolysis temperature is 500°C to 1100°C, and the insulation time is 1h to 3h; Preferably, the heating rate of the pyrolysis is 5°C / min to 10°C / min.
11. Use of the magnesium oxide-loaded and copper-carbon nanomaterial according to any one of claims 1 to 4 in preparing a material for treating melanoma and promoting skin wound repair.